Menakar Reaksi Pasar Saham Jelang dan Pasca Pemilu 2024: Pendekatan Wilcoxon terhadap Trading Volume Activity - Yeza, Aura Hayyu Indah; Yusuf, M.; Lupikawaty, Marieska (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
This study analyses the difference in Trading Volume Activity (TVA) of issuers involved in the Ibu Kota Nusantara (IKN) development before and after Indonesia's 2024 presidential election. Using an event study approach, observations were made over 10 days before and after the election. The research used secondary quantitative data, including stock trading volume, number of shares outstanding, daily closing prices, and the Indonesia Composite Index (IHSG). A purposive sampling method was used to select 62 issuers. The Wilcoxon signed-rank test with SPSS 21 was applied to test the hypothesis. Results show a significant difference in TVA, indicating a positive capital market response to the 2024 election, suggesting high information content. Future research should consider a larger sample, more complex analysis, and a shorter observation period (e.g., 5 days) to minimise non-political influences such as dividends or stock splits. Investors are advised to consider issuer-specific factors and not rely solely on political events, as not all events provide strong decision-making signals. Keywords: trading volume activity, event study, 2024 presidential election, capital market reaction